Negotiating the dual path of HP skiing and post-secondary education: 2 athlete profiles (2015)
A rigorous training schedule comes with many sacrifices, and for many athletes this means forgoing either traditional post-secondary education or the pursuit of skiing. While there is increasing pressure on athletes to choose between the dual paths of higher education and HP skiing, education for the HP athlete does not have to stop after high school, however choosing both requires an adequate supportive network, a conscious decision by the athlete to find balance between the dual paths and sound self-discipline.